Pemanfaatan limbah kulit kopi liberika di Kabupaten Tanjung Jabung Barat, Jambi dan eksplorasi ultrasound-assisted extraction: Fondasi pelestarian budaya lokal untuk daya saing global - Rizki, Tri; Dwi Pasca, Bella; Maharani, Putri; Anggraini, Anna; Sevina, Raisa; Kawuri Putri, Satiti; Anggraini, Rani; Anggi Safira, Doani; Tresnadiana Herlina, Vika (Proceedings Academic Universitas Jambi, 2025)
Liberica coffee husk waste from Tanjung Jabung Barat Regency, Jambi, is a major by-product of coffee processing with high potential as a source of valuable bioactive compounds, yet its utilization remains limited. This study aimed to evaluate ultrasound-assisted extraction (UAE) using three solvents—70% ethanol, 96% ethanol, and methanol—for recovering bioactive compounds from Liberica coffee husk. A quantitative experimental design with three treatments and four replications was applied. Husk simplicia were extracted using UAE, and the resulting extracts were analyzed for yield, color, antioxidant capacity (DPPH), and total phenolic content (Folin–Ciocalteu method). Data were analyzed using ANOVA (5%) followed by Duncan’s New Multiple Range Test. The results showed that 96% ethanol produced the highest yield (17.10% ± 4.10), while methanol yielded the lowest (7.15% ± 0.31). Ethanol extracts were dark reddish-black, whereas methanol extracts appeared lighter. The strongest antioxidant activity was obtained with 70% ethanol (65.98% inhibition), while methanol produced the highest phenolic content (70.32 µg GAE/mL). These findings demonstrate that solvent polarity significantly affects extraction efficiency: aqueous ethanol favored antioxidant activity, while methanol enhanced phenolic recovery. Overall, UAE effectively improved the recovery of bioactive compounds from Liberica coffee husk waste. Extraction with 70% ethanol yielded 16.52% ± 8.56%, produced a reddish-brown extract, showed an antioxidant capacity of 65.98% ± 0.05%, and contained 50.68 ± 4.17 µg GAE/mL phenolics. This study highlights the potential of UAE for valorizing Liberica coffee husk waste into functional food and cosmetic ingredients, promoting waste reduction and supporting a circular economy.